Cognitive, emotional, physical, and behavioral stress-related symptoms and coping strategies among university students during the third wave of COVID-19 pandemic - Attia, Merna; Ibrahim, Fatma A.; Elsady, Mohamed Abd-Elfatah; Khorkhash, Mohamed Khaled; Rizk, Marwa Abdelazim; Shah, Jaffer; Amer, Samar A. (Frontiers in Psychiatry, 2022)
Background: Stress is manifested by different physical, cognitive, emotional, and behavioral stress-related symptoms, and everyone experiences it uniquely. The COVID-19 Pandemic has tremendously affected university students' lives. So, we conducted this study to determine the stress frequency, causes, determinants, and related symptoms involving physical, cognitive, emotional, and behavioral traits and coping strategies among university students in Egypt during the third wave of the COVID-19 pandemic, 2021. Methods: cross-sectional study targeted 1467 randomly selected undergraduate university students, representing all colleges from 30 universities in Egypt, through a validated self-administrated questionnaire. Results: The total stress-related symptom score was statistically significant (p < 0.05), higher among females, married, living on campus, with a (B) GPA, and those who had both organic and psychological disorders. The top ten prevalent physical symptoms were headaches, chronic fatigue, hair loss, low back pain, neck pain, shoulders and arm pain, ophthalmological symptoms, acne, shakiness of extremities, and palpitations, respectively. The most reported symptoms regarding the cognitive, emotional, and behavioral aspects were anxiety and racing thoughts, moodiness and irritability, and excessive sleeping, respectively. 937 (63.9%) reported that the COVID-19 pandemic badly affected their lives, either directly or indirectly. The study showed that the prevalence of stress among university students is more than 97%. One thousand and five (68.5%) preferred isolation as a relieving technique. Conclusion: Stress and its related physical, cognitive, emotional, and behavioral symptoms are prevalent among university students. Most of the university students who were recruited reported that the COVID-19 pandemic badly affected their lives and used negative ways to deal with stress, like staying alone and sleeping too much. Positive ways to deal with stress, like seeing a therapist or meditating, were less common. Keywords: Physical stress-related symptoms, cognitive stress-related symptoms, emotional stress-related symptoms, behavioral stress-related symptoms, university students, COVID-19 pandemic.